2016
DOI: 10.5194/tc-2016-100
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Permafrost Distribution Modeling in the Semi-Arid Chilean Andes

Abstract: Abstract. Mountain permafrost and rock glaciers in the dry Andes are of growing interest due to the increase in human activities in this remote area. Empirical models of mountain permafrost distribution based on the spatial analysis of intact and relict rock glaciers and mean annual air temperature (MAAT) have been established as a tool for regional-scale assessments of permafrost favorability across entire mountain ranges; however, this kind of model approach has never been applied for a large portion of the … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 1 publication
1
8
0
Order By: Relevance
“…This work focuses on the detection of active periglacial phenomena, and not on the determination of their magnitude of displacement. Therefore, the range of detectable displacement, from 2.2 cm/year to 170 cm/year, almost covers the entire displacement values recorded in the literature for the observed phenomena [5,10,19]. In particular, rock glaciers do not exceed point displacements of more than 300-400 cm/year [22].…”
Section: Sentinel-1 Dinsar Applied To Dry Andessupporting
confidence: 66%
See 2 more Smart Citations
“…This work focuses on the detection of active periglacial phenomena, and not on the determination of their magnitude of displacement. Therefore, the range of detectable displacement, from 2.2 cm/year to 170 cm/year, almost covers the entire displacement values recorded in the literature for the observed phenomena [5,10,19]. In particular, rock glaciers do not exceed point displacements of more than 300-400 cm/year [22].…”
Section: Sentinel-1 Dinsar Applied To Dry Andessupporting
confidence: 66%
“…On the other hand, an inactive rock glacier is not in thermal equilibrium with the environment and slowly loses its internal ice as it melts, introducing new water to the active part of hydrologic cycle. Furthermore, both Roer and Nyenhuis [9] and Azócar [10] have shown that the geomorphological, geomorphometric, and environmental or ecological parameters are more useful to discriminate between active or relict rock glaciers than between active or inactive glaciers. Moreover, some of the parameters used are in situ measurements, an important constraint for regional applications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite general awareness on the limitations involved with drawing clear‐cut boundaries between active, inactive and relict categories, this classification scheme is the most widely adopted in rock glacier studies (e.g. Imhof, ; Putnam and Putnam, ; Angillieri, ; Scapozza and Mari, ; Lilleøren and Etzelmüller, ; Scotti et al, ; Azócar, ; Bornet, ; Onaca et al, ).…”
Section: Degree Of Activity (Or Dynamic Classification)mentioning
confidence: 99%
“…Mountain pedoclimate is recognized as a phenomenon that may influence slope stability and hydrology, but knowledge about its characteristics and response to climatic change is still very limited, especially for low latitudes. In the high Andes, this lack of knowledge is greater, and the Central Andes cryosphere is a zone of growing interest . Long‐term in situ measurements of periglacial processes north of 30°S in the Andes are still missing, and permafrost outside rock glaciers remains unexplored .…”
Section: Introductionmentioning
confidence: 99%